Di-l-methacrylato-j4O:O0-bis[aquabis(1,10-phenanthroline-j2N,N0)-copper(II)] dinitrate dihydrate - Tarafder, Md. Tofazzal Hossain; Reza, M. Y.; Crouse, Karen Anne; Suchada, Chantrapromm; Fun, Hoong Kun (International Union of Crystallography, 2008)
The title complex, [Cu2(C4H5O2)2(C12H8N2)2(H2O)2](NO3)2- 2H2O, contains a dimeric [Cu2(C4H5O2)2(C12H8N2)2- (H2O)2]2+ dication with two five-coordinated CuII ions linked by two methacrylate ions in a syn–syn bridging arrangement.The dication possesses pseudo-twofold rotational symmetry.The pentacoordination of each CuII ion has a distorted squarepyramidal geometry, with two N donors from a phenanthroline ligand and two carboxylate O atoms occupying basal sites and the apical position being occupied by a water molecule. In the crystal packing, molecules are linked to form a threedimensional framework by O—H O and C—H O hydrogen bonds and – interactions [centroid–centroid distances of 3.6039 (15), 3.5301 (15), 3.6015 (15),3.6496 (15) and 3.6858 (15) A ° ].